MECHANISMS OF LITHOSPHERIC REJUVENATION ASSOCIATED WITH CONTINENTAL OROGENY - Houseman G.; Molnar P. (My University, 2001)
Gravitational instability of the continental lithospheric mantle is often associated with orogenic activity. Recent theoretical and experimental developments in the understanding of the convective instability of a dense layer, with non-Newtonian viscosity (representing lithosphere) above a less dense fluid layer (representing asthenosphere) are reviewed. These developments offer an explanation for why the continental lithospheric mantle might be generally mechanically stable in spite of a thermally induced density stratification, which one might expect to be unstable, Gravitational stability of this system depends on the initial amplitude of a disturbance to the stratified system, a disturbance that is most likely to be provided by localized lithospheric thickening associated with plate convergence. If the constitutive law that describes the deformation of dry olivine is applicable to the subcontinental mantle, the perturbation required to produce instability could be created by localized horizontal shortening of the order of 10%. If the wet olivine flow law is applicable, the required amount of shortening may be on the order of only 1%, in each case provided that it occurs in a time short compared with the thermal diffusion timescale of the lithosphere. The long-term stabilization of continental lithosphere may thus be associated with dehydration. Under circumstances of localized lithospheric convergence, the buoyancy of the continental crust plays an important role in determining the form of downwelling. If the crust is strong compared to mantle lithosphere, instability generally takes the form of localized downwelling beneath the centre of the convergent zone. If the crust is weak compared to mantle lithosphere, downwelling commences on the margins of the convergent zone as the buoyant crustal layer resists thickening. The initial instability may then trigger rapid extension of the lithospheric mantle beneath the convergent orogen. The extension is driven by asymmetric cold downwellings that move away from the centre of the convergent zone in a way that bears some resemblance to a delaminating slab or a retreating subduction zone. With these results in mind, some of the geological and geophysical evidence for lithospheric instability in modern orogens of Southern California, the South Island of New Zealand, the Mediterranean, and Central Asia are reviewed. Seismological evidence from Southern California and New Zealand suggest that these young orogens provide examples of lithospheric instability, in which downwelling occurs beneath the centre of the convergent zone where the crustal thickening is maximum. In contrast, the Alboran Sea and Tyrrhenian Sea basins show that extension has followed convergence as downwelling has retreated away from the convergent zone, and lithospheric mantle beneath the centre of convergence apparently has been replaced by asthenosphere. The Tien Shan and Tibetan Plateau provide large modern-day examples of continental convergence. In each case there is strong evidence that the mantle lithosphere has undergone some form of instability that has led to at least part of it being replaced by hot asthenosphere. Images provided by teleseismic tomography of variations of seismic wave speeds beneath these orogens suggest that mantle lithosphere has been locally renewed following gravitational instability triggered by orogenic convergence.